A living wage : American workers and the making of consumer society - Glickman, Lawrence B., 1963- (Cornell University Press, 1997)
"A Living Wage," the rallying cry of union activists, is a concept with a revealing history, here documented by Lawrence B. Glickman. The labor movement's response to wages shows how American workers negotiated the transition from artisan to consumer, opening up new political possibilities for organized workers. At the same time, however, they created contradictions that continue to haunt the labor movement today. Nineteenth-century workers saw wages as dangerous, Glickman reveals, because workers hoped to become self-employed artisans rather than permanent employees